The effect of rice types on chao properties during fermentation - Meysi Azkiyah; Amran Laga; Meta Mahendradatta; Riku Shimomura (Hasanuddin University Food Science and Technology Study Program, 2021)
Chao is a typical Indonesian dish from Pangkep Regency that is relatively unknown to the general public. Chao is made from fermented fish, which is subsequently fermented with rice. Chao has the properties of pasta-like, light-brown color, unique flavor, slightly acidic and salty taste. Pangkep communities typically use chao as a seasoning, condiment ingredient, or as a side dish. Due to the product's attractive features, which resemble stale food, make it less appealing to consumers. It necessitates innovation and processing technologies in order to improve the quality of Chao products. This research aimed to find out the effect of rice variations including white rice, red rice and black rice on the characteristics of Shrimp Chao during fermentation. The testing parameters in this study were total Lactic Acid Bacteria (LAB), total lactic acid, pH, and organoleptic. The highest LAB growth was found in the red rice that is 7.67 log cfu/g with the lowest pH value of 6.02 and the highest lactic acid content (1.8%). The best organoleptic test results own by white rice-based shrimp chao with preference average score of 3.85 and red rice 3.78 which imply “like” in organoleptic scale scoring.